HUBUNGAN ANTARA KURANG ENERGI KRONIS (KEK) DENGAN KEJADIAN ANEMIA, PENYAKIT INFEKSI, DAN DAYA KONSENTRASI PADA REMAJA PUTRI - Tri Khayatunnisa (Program Studi Ilmu Gizi, Jurusan Kesmas Fakultas Ilmu-Ilmu Kesehatan Universitas Jenderal Soedirman, 2021)
Chronic Energy Deficiency (CED) is one of the nutritional problems in female adolescents which is marked by the size of the Upper Arm Circumference (MUAC) <23.5 cm. CED problems will have an impact on the incidence of anemia, infectious diseases, and the concentration ability of female adolescents. This research aimed to knowing the relationship between CED with the incidence of anemia, infectious disease, and concentration power in female adolescents. The research method was observational analytic with cross sectional approach. The sampling technique is purposive sampling. The study was conducted on female adolescents at SMK Swagaya 1 Purwokerto through online on the questionnaires for anemia and infectious diseases using google form and for measuring the concentration ability used the grid concentration test which was made on website. Bivariate analysis using chi square test. As many as 56% of respondents experienced KEK, 54% of respondents had anemia, 37% had infectious disease in the past a month, and 79% had less concentration ability. The results of bivariate analysis showed that there was relationship between CED with the concentration ability (p = 0.036, OR = 0.321), there was no relationship between CED with the incidence of anemia (p = 0.759), and infectious disease (p = 0.121). There is relationship between CED with the concentration ability, and there is no relationship between CED with the incidence of anemia and infectious diseases.